CDX2 regulation by the RNA-binding protein MEX3A: impact on intestinal differentiation and stemness - Pereira, Bruno (2018)
The homeobox transcription factor CDX2 plays a crucial role in intestinal cell fate specification, both during normal development and in tumorigenic processes involving intestinal reprogramming. The CDX2 regulatory network is intricate, but it has not yet been fully uncovered. Through genome-wide screening of a 3D culture system, the RNA-binding protein MEX3A was identified as putatively involved in CDX2 regulation; therefore, its biological relevance was addressed by setting up cell-based assays together with expression studies in murine intestine. We demonstrate here that MEX3A has a repressive function by controlling CDX2 levels in gastric and colorectal cellular models. This is dependent on the interaction with a specific binding determinant present in CDX2 mRNA 3'untranslated region. We have further determined that MEX3A impairs intestinal differentiation and cellular polarization, affects cell cycle progression and promotes increased expression of intestinal stem cell markers, namely LGR5, BMI1 and MSI1. Finally, we show that MEX3A is expressed in mouse intestine, supporting an in vivo context for interaction with CDX2 and modulation of stem cell properties. Therefore, we describe a novel CDX2 post-transcriptional regulatory mechanism, through the RNA-binding protein MEX3A, with a major impact in intestinal differentiation, polarity and stemness, likely contributing to intestinal homeostasis and carcinogenesis.